Hyperelastic aerogel sensing material as well as preparation method and application thereof
A superelastic aerogel sensing material is developed by combining cellulose and lignin with conductive enhancements, addressing poor elasticity and sensitivity issues, achieving high sensitivity, fast responsiveness, and stable signal transmission.
Patent Information
- Application Number
- CN202411296005.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Existing aerogel-based sensors suffer from poor elasticity, low sensitivity, poor signal stability, and prolonged response times due to insufficient substrate elasticity and limited contact resistance changes, making them unsuitable for high-performance applications.
A superelastic aerogel sensing material is prepared by combining cellulose and lignin as gel precursors, with a designed molecular segment and pore structure, and enhanced with conductive active substances through a series of chemical processes including cross-linking, freezing, and thermal chemical vapor deposition to achieve high sensitivity, fast responsiveness, and wide detection range.
The resulting aerogel exhibits over 99% height recovery after 100 cycles, a wide detection range of 0.01% strain to 74% strain, sensitivity factors up to 3364, and response times of 9 to 11 ms, with signal retention rates exceeding 90% in 1000 cycles.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of intelligent soft materials, and specifically relates to a superelastic aerogel sensing material and a preparation method and application thereof. Background Art
[0002] With the booming development of artificial intelligence, human-computer interaction, the Internet of Things, and wearable electronics, there is an urgent need for high-performance pressure sensors with ultra-high sensitivity and adjustable mechanical properties. Compared with other types of sensors, piezoresistive sensors composed of elastic substrates and conductive materials have excellent sensitivity, fast response, and signal stability to stress / strain-induced changes, and are ideal candidates for next-generation pressure sensors. Lightweight aerogels with adjustable microporous structures, low density, high porosity, and high surface area are ideal substrates for the development of high-performance piezoresistive sensors. However, aerogel-based sensors generally have problems with insufficient substrate elasticity and limited contact resistance changes, resulting in reduced sensitivity, limited detection range, and prolonged response time.
[0003] Biomass aerogel is the third generation of aerogel. It has the advantages of rich precursors, low cost, rich functional groups, easy modification and biodegradability. It is widely used in thermal insulation materials, oil-water separation materials and sensor substrates. However, biomass aerogels generally have problems such as poor mechanical properties, low structural strength and poor elasticity, which limit their promotion in large-scale applications. In the research field of biomass-based aerogels, cellulose-based aerogels have become a hot topic of research due to their outstanding properties. Cellulose is a linear polymer composed of β-glucose connected by β-1,4-glycosidic bonds. It has rich oxygen-containing functional groups and is an ideal aerogel precursor. Fu Daning of South China University of Technology disclosed a superelastic, highly conductive multifunctional aerogel based on nanocellulose and its preparation method and application (CN115368622B). The method uses chitosan (CS) to enhance the structural strength of cellulose nanofiber (CNF) aerogel to prepare a superelastic, highly conductive multifunctional aerogel. Although this aerogel exhibits excellent sensing performance, the preparation process of its raw material CNF is relatively complicated and costly, and CS has limited effect on the elastic enhancement of CNF aerogel. Chen et al. (Advanced Functional Materials 2020, 30, 1910292) introduced lignin into cellulose nanofiber aerogel to enhance the network strength of cellulose aerogel, so that it can maintain its gel network structure during carbonization. The constructed high elastic carbon aerogel can be used for stress / strain sensing, but the preparation process of CNF is complicated and the energy consumption of the carbonization process is high. The assembled sensor has low sensitivity and poor elasticity. Shi Zhuqun of Wuhan University of Technology disclosed a nanocellulose / Ti3C2T~X composite aerogel and its preparation method and application (CN114588846A). The aerogel has good high compressive elasticity and conductivity, but the preparation process of Ti3C2T~X is complicated, and the interaction between it and the aerogel is weak. In multiple cycles, Ti3C2T~X is easy to fall off, resulting in unstable signals.
[0004] Lignin is one of the most abundant aromatic biomacromolecules in nature, with a unique three-dimensional multi-benzene ring rigid molecular structure. In addition, multiple functional groups such as phenolic hydroxyl, alcoholic hydroxyl, and carboxyl are embedded in the three-dimensional structure of lignin, making it an ideal green cross-linking agent. The high rigidity of lignin combined with its unique three-dimensional multifunctionality makes it an ideal structural reinforcer for cellulose aerogels, which helps to improve the mechanical properties and stability of aerogels while maintaining their environmentally friendly properties.
[0005] In general, aerogels composed of flexible polymers show good flexibility, but due to the lack of reinforcement of rigid molecular segments, their elasticity is usually unsatisfactory. In contrast, although aerogels composed of rigid polymers have excellent mechanical strength, they are often accompanied by high brittleness, which also limits their elasticity. On the other hand, aerogels with large interlayer distances have better elasticity, but they usually cannot establish effective conductive pathways under low pressure, resulting in problems such as low sensitivity, high detection limit and long response time. For example, Zhang et al. (Small 2023, 2310038) introduced conductive carbon black into cellulose submicron fiber aerogels to construct highly elastic conductive aerogels for stress sensing, but the interlayer spacing of the aerogel was large and the dispersion of carbon black in the gel network was poor, resulting in low sensitivity of the aerogel. Wang et al. (Carbohydrate Polymers 270, 2021, 118414) prepared aerogels by combining aramid and nanocellulose and prepared conductive aerogels by loading polypyrrole. However, the aerogel had a large pore spacing and poor dispersion of the conductive active material, which limited the sensitivity and detection range of the aerogel. In addition, too small an interlayer spacing can easily lead to agglomeration of the conductive polymer, thereby reducing the sensitivity of the aerogel sensor. For example, Wu et al. (ACS Applied Polymer Materials 2023, 5, 3938−3948) introduced PEDOT:PSS into cellulose nanofiber aerogel to construct a conductive cellulose aerogel. The aerogel had good signal stability, but the interlayer spacing of the aerogel was small and the pore structure was uneven, resulting in low sensing sensitivity. Therefore, the preparation of high-performance aerogel sensor materials is still challenging. Summary of the invention
[0006] In order to solve the problems of poor elasticity, low sensitivity, poor signal stability and long response time of traditional piezoresistive aerogels, the primary purpose of the present invention is to provide a method for preparing a superelastic aerogel sensing material.
[0007] The present invention uses cellulose as a flexible biomacromolecule and lignin as a rigid biomacromolecule as gel precursors, and prepares a "rigid and flexible" superelastic lignin / cellulose aerogel through the design of molecular segment microstructure and pore structure microstructure. At the same time, the conductive network structure of the aerogel is improved by loading conductive active substances to prepare an aerogel with superelasticity, high sensitivity, fast responsiveness, low hysteresis, wide detection range and high signal stability, solving the problems of poor elasticity, low conductive sensitivity, unstable signal transmission, slow response speed and narrow detection range when cellulose biomass aerogel is used as a sensor. The aerogel is expected to replace petroleum-based aerogel sensing materials and achieve cost reduction and efficiency improvement of aerogel sensor materials.
[0008] Another object of the present invention is to provide a superelastic aerogel sensing material prepared by the above preparation method.
[0009] Another object of the present invention is to provide an application of the above-mentioned superelastic aerogel sensing material.
[0010] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a superelastic aerogel sensing material comprises the following steps: (1) Add cellulose and lignin to a urea / alkali mixed solution, and after fully dissolving, add a cross-linking agent to obtain lignin / cellulose hydrogel (LCEH) through chemical cross-linking. (2) immersing the lignin / cellulose hydrogel in water to make it swell; (3) Directional freezing of the swollen lignin / cellulose hydrogel and freeze-drying to obtain a directional frozen lignin / cellulose composite aerogel (DF-LCEA); (4) The directional frozen lignin / cellulose composite aerogel was first immersed in a pyrrole (Py) / acid mixed solution, then immersed in a ferric chloride / acid mixed solution to induce the in-situ polymerization of pyrrole, and finally freeze-dried to obtain a superelastic conductive lignin / cellulose aerogel (DF-LCEA@PPy); (5) Silane was deposited on the superelastic conductive lignin / cellulose aerogel by thermal chemical vapor deposition to obtain the hydrophobic superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0011] Preferably, the cellulose in step (1) is at least one of hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose.
[0012] Preferably, the lignin in step (1) is at least one of alkali lignin, lignin sulfonate, enzymatic lignin and solvent-based lignin.
[0013] Preferably, the base in step (1) is at least one of sodium hydroxide and potassium hydroxide.
[0014] Preferably, the cross-linking agent in step (1) is at least one of epichlorohydrin, N,N-methylenebisacrylamide and glutaraldehyde.
[0015] Preferably, the mass ratio of cellulose to lignin in step (1) is (1-4):(1-5); more preferably 3:(3-5).
[0016] Preferably, in the urea / alkali mixed solution of step (1), the mass ratio of urea to alkali is (5-15):(5-10), and the total mass concentration of the urea / alkali mixed solution is 15-25%; more preferably, the mass ratio of urea to alkali is (9-14):(5-10).
[0017] Preferably, the concentration of the cross-linking agent in step (1) in the system of step (1) is 3-15 wt %, that is, the percentage of the cross-linking agent to the total mass of lignin, cellulose, urea / alkali mixed solution and cross-linking agent is 3-15%.
[0018] Preferably, the ratio of the cellulose to the urea / alkali mixed solution in step (1) is (1-4) g:100 mL; more preferably (2-4) g:100 mL.
[0019] Preferably, the swelling time in step (2) is 6 to 48 hours, more preferably 6 to 24 hours.
[0020] Preferably, the directional freezing method in step (3) is a liquid nitrogen-assisted directional freezing method, specifically placing the swollen lignin / cellulose hydrogel on a copper plate immersed in liquid nitrogen for directional freezing.
[0021] Preferably, the freeze-drying temperature in step (3) is -50 to -90°C, the pressure is 1 to 10 Pa, and the freeze-drying time is 36 to 48 hours.
[0022] Preferably, the concentration of pyrrole in the pyrrole (Py) / acid mixed solution in step (4) is 0.1-2wt%, more preferably 0.5-2wt%, most preferably 1-2wt%; the immersion time is 10 minutes to 12 hours, more preferably 10 minutes to 2 hours, most preferably 30 to 60 minutes; the acid is one of 0.1-1mol / L hydrochloric acid and 0.1-1mol / L sulfuric acid, most preferably 0.1-1mol / L hydrochloric acid.
[0023] The pyrrole (Py) / acid mixed solution in step (4) is obtained by adding pyrrole into an acid solution and mixing; the ferric chloride / acid mixed solution is obtained by adding ferric chloride into an acid solution and mixing.
[0024] Preferably, the concentration of ferric chloride in the ferric chloride / acid mixed solution in step (4) is 0.1 to 3 mol / L, more preferably 0.5 to 3 mol / L, most preferably 0.5 to 2.5 mol / L; the soaking time is 0.5 to 12 hours, more preferably 0.5 to 6 hours; the acid is one of 0.1 to 1 mol / L hydrochloric acid and 0.1 to 1 mol / L sulfuric acid, most preferably 0.1 to 1 mol / L hydrochloric acid.
[0025] Preferably, the temperature of the ferric chloride / acid mixed solution in step (4) is -5 to 5°C.
[0026] Preferably, the freeze drying in step (4) refers to first freezing at -30 to -18°C for 12 to 48 hours and then freeze drying at -50 to -90°C and 1 to 10 Pa for 36 to 52 hours.
[0027] Preferably, the thermal chemical vapor deposition method in step (5) is: placing the superelastic conductive lignin / cellulose aerogel and silane in the same container, heating, and depositing the silane on the superelastic conductive lignin / cellulose aerogel.
[0028] More preferably, the silane is at least one of methyltrimethoxysilane and methyltrichlorosilane, more preferably methyltrimethoxysilane.
[0029] More preferably, the ratio of the silane to the superelastic conductive lignin / cellulose aerogel is 0.5-2 mL: 0.1-2 g; the heating temperature is 50-80° C., more preferably 60-70° C.; the heating time is 2-24 hours, more preferably 3-12 hours.
[0030] The superelastic aerogel sensing material prepared by the above preparation method.
[0031] Application of the above-mentioned superelastic aerogel sensing material.
[0032] Preferably, the application is application in stress sensors and strain sensors.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The superelastic aerogel sensing material provided by the present invention has a height recovery rate of more than 99% after 100 cycles under 50% strain, a maximum stress retention rate of more than 97%, and an energy loss rate of less than 57% in the first cycle.
[0034] 2. The superelastic aerogel sensing material provided by the present invention has a wide detection limit. As a strain sensor, its detection range is 0.01% strain to 74% strain. As a stress sensor, its detection range is 4.6 Pa to 30.0 kPa.
[0035] 3. The superelastic aerogel sensing material provided by the present invention has extremely high sensitivity. As a strain sensor, its sensitivity factor can reach 3364, and its linear correlation coefficient is 0.9977; as a stress sensor, its sensitivity can reach 160.34 kPa -1 , and its linear correlation coefficient is 0.9971.
[0036] 4. The superelastic aerogel sensing material provided by the present invention has an extremely fast response time, with a compression response time of 9 to 11 ms and a rebound response time of 38 to 50 ms.
[0037] 5. The superelastic aerogel sensing material provided by the present invention has excellent cyclic signal stability. In 1000 cycle experiments under 15% strain, the signal retention rate is higher than 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a scanning electron microscope image of the cross section of the aerogel prepared in Example 1.
[0039] Figure 2 This is a scanning electron microscope image of the longitudinal section of the aerogel prepared in Example 1.
[0040] Figure 3 is the pore wall thickness of the aerogel prepared in Example 1.
[0041] Figure 4 The results of the maximum stress retention rate and the energy loss rate of the first cycle in the cyclic compression test of the aerogels prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, and Example 9 are summarized.
[0042] Figure 5 The height recovery rate of the aerogel prepared in Example 1 under different compressive strains.
[0043] Figure 6 The maximum stress retention rate and the first cycle energy loss rate of the aerogel prepared in Example 1 after 100 cycles at 50% strain.
[0044] Figure 7 This is a sensitivity test of the aerogels prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8 and Example 9.
[0045] Figure 8 This is a diagram showing the resistivity change of the aerogel prepared in Example 1 under different dynamic strains.
[0046] Fig. 9 This is the signal stability of the aerogel prepared in Example 1 at different stress application speeds.
[0047] Fig.10 The sensitivity of the aerogel prepared in Example 1 as a stress sensor.
[0048] Fig.11The sensitivity of the aerogel prepared in Example 1 as a strain sensor.
[0049] Fig.12 This is the sensing response speed of the aerogel prepared in Example 1.
[0050] Fig.13 This is the sensing lag time of the aerogel prepared in Example 1.
[0051] Fig.14 This is the cyclic signal stability of the aerogel prepared in Example 1. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0053] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0054] Example 1 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.1 mL of epichlorohydrin to the above solution, stir for 150 seconds, pour into a cube-shaped mold and let stand to allow it to completely gel.
[0055] (2) The prepared hydrogel was immersed in deionized water for 24 hours to allow it to fully swell.
[0056] (3) Using liquid nitrogen as a cold source, the swollen hydrogel is placed on a copper plate immersed in liquid nitrogen for directional freezing until it is completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying to prepare aerogel.
[0057] (4) The aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 6 h. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0058] (5) The PPy-loaded aerogel was placed in a dryer containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a 70 °C forced air oven for 12 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0059] Example 2 (1) Add 0.3 g of carboxymethyl cellulose and 0.3 g of lignin sulfonate to 10 mL of 6 / 13 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.3 mL of epichlorohydrin to the above solution, stir for 120 seconds, pour into a cube-shaped mold and let stand to allow it to completely gel.
[0060] (2) The prepared hydrogel was immersed in deionized water for 36 hours to allow it to fully swell.
[0061] (3) Using liquid nitrogen as a cold source, the swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying for 36 hours to prepare aerogel.
[0062] (4) The above aerogel was immersed in a 2 wt% pyrrole (Py) / 0.5 mol / L sulfuric acid mixed solution for 10 min, and then the aerogel adsorbed with Py was immersed in a 0°C 1.0 mol / L ferric chloride / 0.5 mol / L sulfuric acid mixed solution for 12 h. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 52 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0063] (5) The PPy-loaded aerogel was placed in a desiccator containing 1 mL of methyltrichlorosilane (TMCS) and heated in a forced air oven at 50 °C for 24 h to deposit MTMS on DF-LCEA@PPy to obtain a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0064] Example 3 (1) Add 0.2 g of hydroxyethyl cellulose and 0.2 g of alkali lignin to 10 mL of 10 / 9 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.5 mL of epichlorohydrin to the above solution, stir for 100 seconds, and pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0065] (2) The prepared hydrogel was immersed in deionized water for 48 hours to allow it to fully swell.
[0066] (3) Using liquid nitrogen as a cold source, the swollen hydrogel is placed on a copper plate immersed in liquid nitrogen for directional freezing until it is completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying to prepare aerogel.
[0067] (4) The above aerogel was immersed in a 0.5 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 20 min, and then the aerogel adsorbed with Py was immersed in a -5°C 1.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution for 3 hours. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. It was then placed in a -58°C, 4 Pa freeze dryer and freeze-dried for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0068] (5) The PPy-loaded aerogel was placed in a dryer containing 1.5 mL of methyltrimethoxysilane (MTMS) and heated in a 50 °C forced air oven for 6 h to deposit MTMS on DF-LCEA@PPy to obtain a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0069] Example 4 (1) Add 0.1 g of hydroxypropyl cellulose and 0.1 g of solvent-based lignin to 10 mL of 5 / 14 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 0.5 mL of epichlorohydrin to the above solution, stir for 120 seconds, pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0070] (2) The prepared hydrogel was immersed in deionized water for 12 hours to allow it to fully swell.
[0071] (3) Using liquid nitrogen as a cold source, the swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen, and then placed in a freeze dryer at -90°C and 4 Pa for freeze drying for 40 hours to prepare aerogel.
[0072] (4) The above aerogel was immersed in a 1.5wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 40 min, and then the aerogel adsorbed with Py was immersed in a 2 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 0.5 h. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0073] (5) The PPy-loaded aerogel was placed in a dryer containing 2 mL of methyltrimethoxysilane (MTMS) and heated in a 60 °C forced air oven for 1 h to deposit MTMS on DF-LCEA@PPy to obtain a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0074] Example 5 (1) Add 0.3 g of hydroxyethyl cellulose and 0.5 g of alkali lignin to 10 mL of 5 / 14 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 0.7 mL of epichlorohydrin to the above solution, stir for 200 seconds, and pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0075] (2) The prepared hydrogel was immersed in deionized water for 6 hours to allow it to fully swell.
[0076] (3) Using liquid nitrogen as a cold source, the swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying for 42 hours to obtain a superelastic aerogel.
[0077] (4) The above aerogel was immersed in a 2 wt% pyrrole (Py) / 0.5 mol / hydrochloric acid mixed solution for 50 min, and then the aerogel adsorbed with Py was immersed in a 2.5 mol / L ferric chloride / 0.5 mol / hydrochloric acid mixed solution at 0°C for 1.5 hours. Then, the DF-LCEA loaded with polypyrrole (PPy) was placed in a -18°C refrigerator and frozen for 24 hours, and then placed in a -58°C, 4Pa freeze dryer for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0078] (5) The PPy-loaded aerogel was placed in a desiccator containing 1.5 mL of methyltrimethoxysilane (MTMS) and heated in a forced air oven at 60 °C for 2 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0079] Example 6 (1) Add 0.4 g of hydroxypropyl methylcellulose and 0.4 g of alkali lignin to 10 mL of 8 / 11 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 0.9 mL of epichlorohydrin to the above solution, stir for 200 seconds, and pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0080] (2) The prepared hydrogel was immersed in deionized water for 32 hours to allow it to fully swell.
[0081] (3) Using liquid nitrogen as a cold source, the swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying for 48 hours to obtain a superelastic aerogel.
[0082] (4) The above aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 60 min, and then the aerogel adsorbed with Py was immersed in a 3.0 mol / L ferric chloride / 0.5 mol / hydrochloric acid mixed solution at 0°C for 3 hours. Then, the DF-LCEA loaded with polypyrrole (PPy) was placed in a -18°C refrigerator and frozen for 24 hours, and then placed in a -58°C, 4 Pa freeze dryer for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0083] (5) The PPy-loaded aerogel was placed in a dryer containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a forced air oven at 80 °C for 3 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0084] Example 7 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 10 / 9 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.3 mL of epichlorohydrin to the above solution, stir for 150 seconds, and pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0085] (2) The prepared hydrogel was immersed in deionized water for 6 hours to allow it to fully swell.
[0086] (3) Using liquid nitrogen as a cold source, the swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying for 45 hours to obtain a superelastic aerogel.
[0087] (4) The above aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 120 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 9 hours. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0088] (5) The PPy-loaded aerogel was placed in a dryer containing 1.5 mL of methyltrimethoxysilane (MTMS) and heated in a forced air oven at 65 °C for 24 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0089] Example 8 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.1 mL of 0.1 g / mL N,N-methylenebisacrylamide to the above solution, stir for 100 seconds, and pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0090] (2) The prepared hydrogel was immersed in deionized water for 24 hours to allow it to fully swell.
[0091] (3) Using liquid nitrogen as a cold source, the swollen hydrogel is placed on a copper plate immersed in liquid nitrogen for directional freezing until it is completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying to prepare aerogel.
[0092] (4) The aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 6 h. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0093] (5) The PPy-loaded aerogel was placed in a dryer containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a 70 °C forced air oven for 12 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0094] Example 9 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 6 / 13 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 0.5 mL of glutaraldehyde to the above solution, stir for 30 seconds, pour into a cube-shaped mold and let it stand to allow it to completely gel.
[0095] (2) The prepared hydrogel was immersed in deionized water for 24 hours to allow it to fully swell.
[0096] (3) Using liquid nitrogen as a cold source, the swollen hydrogel is placed on a copper plate immersed in liquid nitrogen for directional freezing until it is completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying to prepare aerogel.
[0097] (4) The aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 5°C for 6 h. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a superelastic conductive lignin / cellulose composite aerogel.
[0098] (5) The PPy-loaded aerogel was placed in a dryer containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a 70 °C forced air oven for 12 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0099] Comparative Example 1 (1) Add 0.4 g of hydroxyethyl cellulose to 10 mL of 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.1 mL of epichlorohydrin to the above solution, stir for 150 seconds, pour into a cube-shaped mold and let stand to allow it to completely gel.
[0100] (2) The prepared hydrogel was immersed in deionized water for 24 hours to allow it to fully swell.
[0101] (3) Using liquid nitrogen as a cold source, the swollen hydrogel is placed on a copper plate immersed in liquid nitrogen for directional freezing until it is completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying to prepare aerogel.
[0102] (4) The above aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 6 hours. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a conductive cellulose aerogel.
[0103] (5) The PPy-loaded aerogel was placed in a desiccator containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a forced air oven at 70 °C for 12 h to deposit MTMS on DF-LCEA@PPy to obtain a hydrophobic-conductive cellulose aerogel sensing material (S-DF-CEA@PPy).
[0104] Comparative Example 2 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.1 mL of epichlorohydrin to the above solution, stir for 150 seconds, pour into a cube-shaped mold and let stand to allow it to completely gel.
[0105] (2) The prepared hydrogel was immersed in deionized water for 24 hours to allow it to fully swell.
[0106] (3) The swollen hydrogel was placed in a -18°C refrigerator for 24 hours, and then freeze-dried in a -58°C, 4 Pa freeze dryer for 48 hours to prepare aerogel.
[0107] (4) The above aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 6 hours. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. After that, it was placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a conductive cellulose aerogel.
[0108] (5) The PPy-loaded aerogel was placed in a desiccator containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a forced air oven at 70 °C for 12 h to deposit MTMS on DF-LCEA@PPy to obtain a hydrophobic-conductive cellulose aerogel sensing material (S-DF-CEA@PPy).
[0109] Comparative Example 3 (1) 0.4 g hydroxyethyl cellulose and 0.4 g alkali lignin were added to 10 mL 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and magnetically stirred until completely dissolved. The solution was then poured into a cubic mold. Liquid nitrogen was used as a cold source. The swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen. The aerogel was then placed in a freeze dryer at -58°C and 4 Pa for freeze drying for 48 hours to prepare aerogel.
[0110] (2) The above aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 6 hours. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours, and then placed in a -58°C, 4Pa freeze dryer for 48 hours for freeze drying to obtain a conductive cellulose aerogel.
[0111] (3) The PPy-loaded aerogel was placed in a dryer containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a 70 °C forced air oven for 12 h to deposit MTMS on DF-LCEA@PPy to obtain a hydrophobic-conductive cellulose aerogel sensing material (S-DF-CEA@PPy).
[0112] Comparative Example 4 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then add 1.1 mL of epichlorohydrin to the above solution, stir for 150 seconds, pour into a cube-shaped mold and let stand to allow it to completely gel.
[0113] (2) Using liquid nitrogen as a cold source, the hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen, and then placed in a freeze dryer at -58°C and 4 Pa for freeze drying for 48 hours to prepare aerogel.
[0114] (3) The above aerogel was immersed in a 1 wt% pyrrole (Py) / 0.5 mol / L hydrochloric acid mixed solution for 30 min, and then the aerogel adsorbed with Py was immersed in a 0.5 mol / L ferric chloride / 0.5 mol / L hydrochloric acid mixed solution at 0°C for 6 hours. The DF-LCEA loaded with polypyrrole (PPy) was then placed in a -18°C refrigerator and frozen for 24 hours. It was then placed in a -58°C, 4Pa freeze dryer and freeze-dried for 48 hours to obtain a conductive cellulose aerogel.
[0115] (4) The PPy-loaded aerogel was placed in a desiccator containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a forced air oven at 70 °C for 12 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-conductive cellulose aerogel sensing material (S-DF-CEA@PPy).
[0116] Comparative Example 5 (1) Add 0.4 g of hydroxyethyl cellulose and 0.4 g of alkali lignin to 10 mL of 7 / 12 / 81 wt% sodium hydroxide / urea / water solution and stir magnetically until completely dissolved. Then, add 1 ml of pyrrole and 0.05 g of ferric chloride to the above solution.
[0117] (2) After the above solution is stirred evenly, add 1.1 mL of epichlorohydrin to the sol, stir for 150 seconds, and then pour it into a cube-shaped mold and let it stand to allow it to completely gel.
[0118] (3) The prepared hydrogel was immersed in deionized water for 24 hours to allow it to fully swell.
[0119] (4) Using liquid nitrogen as a cold source, the swollen hydrogel was placed on a copper plate immersed in liquid nitrogen for directional freezing until it was completely frozen, and then placed in a -18°C refrigerator for 24 hours and then placed in a -58°C, 4 Pa freeze dryer for 48 hours for freeze drying to obtain aerogel.
[0120] (5) The PPy-loaded aerogel was placed in a dryer containing 1 mL of methyltrimethoxysilane (MTMS) and heated in a 70 °C forced air oven for 12 h to deposit MTMS on DF-LCEA@PPy, thereby obtaining a hydrophobic-superelastic aerogel sensing material (S-DF-LCEA@PPy).
[0121] Test Method 1. Compression modulus and maximum stress were measured using a Universele testing machine. The compression test was conducted at 25°C and 40% relative humidity at a speed of 100 mm•min. -1The rates were carried out at 40% and 50% strain respectively. The maximum stress is directly obtained from the stress-strain curve, and the Young's modulus of the aerogel is calculated from the slope of the linear elastic region on the stress-strain curve. The maximum stress retention rate (MSR) and energy loss rate (ELR) of the aerogel are calculated based on the stress-strain curve. MSR=S L / S0×100%, where S0 is the maximum stress of the first compression cycle; S L is the maximum stress of the last compression cycle. ELR=(W1-W2) / W1×100%, where W1 represents the loading work and W2 represents the unloading work.
[0122] 2. Pressure sensing performance test: Conductive silver paste and copper foil were applied to both ends of the aerogel to make a piezoresistive pressure sensor. The real-time resistance change under different stress / strain was tested using Keithley 2100. Sensitivity reflects the response characteristics of the sensor, and its calculation formula is defined as S=(∆R / R0) / ∆P, where ∆R is the change in aerogel resistance during compression, R0 is the initial resistance before compression, and ∆P represents the change in applied pressure. When used as a strain sensor, the sensitivity is quantified by the sensitivity factor coefficient (GF), which is defined as GF=(∆R / R0) / ε, where ε represents the compressive strain of the aerogel.
[0123] Figure 1 (a) is a cross-sectional scanning electron microscope image of Example 1, showing a three-dimensional interconnected honeycomb-like uniform pore structure with an average pore size of 44.73±10.78 μm. Figure 1 (b) is a cross-sectional SEM image of Comparative Example 2, showing a disordered macroporous structure with an average pore size of 185.21±128.63 μm. Figure 1 (c) is a cross-sectional SEM image of Comparative Example 4, showing a non-porous / closed-pore structure with an average pore size of 185.21±128.63 μm. Figure 1 (a) and Figure 1 As shown in (b), the aerogel pore structure constructed by the liquid nitrogen-assisted directional freezing method using liquid nitrogen as the cold source is more uniform and has a smaller pore size, which indicates that the gel network of the aerogel prepared by the liquid nitrogen-assisted directional freezing method is more uniform. Figure 1 (a) and Figure 1 (c) shows that appropriate swelling time can make the gel network fully swell, increase the uniformity of the gel network and improve the porosity.
[0124] Figure 2 This is a scanning electron microscope image of the longitudinal section of Example 1, showing an oriented vertical porous structure.
[0125] Figure 3 Schematic diagram of the hole wall of Example 1, wherein the average hole wall thickness is 0.52 μm.
[0126] Figure 4 The results of the maximum stress retention rate and the energy loss rate of the first cycle in the cyclic compression test of the aerogels prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Examples 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8 and Example 9 are summarized. Figure 4 It can be seen that the introduction of lignin can effectively enhance the elasticity of aerogel, and its maximum stress retention rate is increased from 52.14% to 99.09%, and the first cycle energy loss rate is reduced from 78.42% to 50.21%. Figures 1 to 4 From the data analysis, it can be clearly observed that the oriented porous structure prepared by the directional freezing method has a significant effect on enhancing the elasticity of the aerogel. Specifically, this structural optimization significantly increases the maximum stress retention rate of the aerogel from 68.79% to 99.09%. At the same time, its energy loss rate in the first cycle is also significantly reduced from 70.24% to 55.21%. These results show that the directional freezing method plays an important role in improving the elasticity and cyclic stability of the aerogel. From Comparative Example 3 and Example 1 and Figure 4 It can be seen that the introduction of epichlorohydrin can effectively enhance the crosslinking degree of the gel system, thereby improving the elasticity of the aerogel network, increasing its maximum stress retention rate from 48.66% to 99.09%, and reducing the first cycle energy loss rate to 55.21%. Figure 4 It can be seen from the data that the swelling process plays a key role in improving the elasticity of aerogels. The experimental results show that the maximum stress retention rate of the aerogels that have been swollen is significantly improved, from 86.24% to 99.09%. In addition, the energy loss rate of the first cycle is also improved, from 61.11% to 55.21%. These data fully demonstrate the significant effect of the swelling process in enhancing the elasticity of aerogels and reducing energy loss. The enhancement of aerogel elasticity may be due to the fact that the swelling process allows the gel network to fully stretch, increases the porosity of the aerogel, and reduces local force concentration during compression. Furthermore, from Example 1 and Comparative Example 5 and Figure 4It can be seen that the order of adding ferric chloride has an important influence on the mechanical strength of the aerogel. Ferric chloride will react with sodium hydroxide to generate ferric hydroxide under alkaline conditions, thereby destroying the uniformity of the gel system, causing its maximum stress retention rate to drop sharply and the energy loss rate to rise sharply. It can be seen from Examples 1, 8 and 9 that epichlorohydrin, N,N-methylenebisacrylamide and glutaraldehyde can all be used as cross-linking agents to prepare highly elastic lignin / cellulose aerogels, among which the aerogel prepared with epichlorohydrin as the cross-linking agent has the best elasticity.
[0127] Figure 5 is the height recovery rate of the aerogel prepared in Example 1 at a strain of 10% to 90%. As can be seen from the figure, the height recovery rate of the aerogel prepared in Example 1 in a wide strain range of 10% to 80% exceeds 90%, which indicates that the aerogel prepared in Example 1 has excellent elastic recovery performance.
[0128] Figure 6 The maximum stress retention rate and the first cycle energy loss rate of the aerogel prepared in Example 1 after 100 cycles at 50% strain. As can be seen from the figure, after the aerogel prepared in Example 1 was cycled 100 times at 50% strain, its maximum stress retention rate reached 99.09%, and there was almost no stress decay. In addition, its energy loss rate was 55.21%, which further proved that the prepared aerogel had excellent elastic recovery performance and excellent fatigue resistance.
[0129] Figure 7The sensitivity test of the aerogels prepared by Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8 and Example 9. It can be seen from Comparative Example 1 and Example 1 that the introduction of lignin to construct a three-dimensional porous structure can effectively improve its sensitivity from GF=415 to GF=1306. In addition, it can be seen from Example 1 and Comparative Example 2 that the uniformly oriented small pore structure constructed by the liquid nitrogen-assisted-directional freezing method is more conducive to the loading of pyrrole and the construction of more conductive contact points than the disordered macroporous structure constructed by the conventional refrigerator freezing method. Therefore, the sensitivity of the aerogel constructed by directional freezing is 3.28 times higher than that of the aerogel constructed by the conventional refrigerator freezing method (from GF=305 to GF=1306). Furthermore, by comparing Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7, it can be seen that the immersion time of pyrrole has a crucial influence on the sensitivity of the aerogel. As the immersion time of pyrrole increases, the sensitivity of the aerogel first increases and then decreases, and reaches a maximum value when the immersion time is 30 minutes. This is because as the immersion time increases, the degree of polymerization of pyrrole increases, and when the immersion time exceeds 30 minutes, pyrrole agglomerates, resulting in a decrease in the sensitivity of the aerogel. By comparing Example 3 with Example 1 and Figure 7 It can be seen that the introduction of epichlorohydrin can effectively improve the sensitivity of the prepared aerogel sensor, increasing it from GF=121 to GF=1306. This is because the addition of epichlorohydrin increases the crosslinking degree of the gel system, increases the porosity, and thus increases the change in contact resistance. Figure 7 It can be seen that the swelling process has a significant effect on improving the sensitivity of aerogel sensors. Specifically, the swelling treatment allows the gel network structure to be fully expanded and the porosity to increase, which increases the loading amount of pyrrole and increases the change in contact resistance. Therefore, the sensitivity of the aerogel sensor that has undergone swelling treatment is significantly improved from GF=86 to GF=1306. This result shows that the swelling process plays a key role in enhancing the performance of aerogel sensors. It can be seen from Examples 1, 8 and 9 that epichlorohydrin, N,N-methylenebisacrylamide and glutaraldehyde can be used as cross-linking agents to prepare highly elastic lignin / cellulose aerogels. Among them, the aerogel prepared with epichlorohydrin as a cross-linking agent has the best sensitivity.
[0130] Figure 8 The resistivity variation diagram of the aerogel prepared in Example 1 under different dynamic strains. Figure 8 It can be seen that the resistance change (ΔR / R0) of the aerogel prepared in Example 1 increases proportionally with the applied pressure. Figure 8It can be seen that the aerogel prepared in Example 1 can stably and effectively distinguish 0.01% strain to 5% strain, which demonstrates the excellent low-strain detection performance of the aerogel prepared in Example 1.
[0131] Fig. 9 This is the signal stability of the aerogel prepared in Example 1 at different stress application speeds. Fig. 9 The aerogels prepared in Example 1 were shown to have a -1 , 100 mm•min -1 , 150 mm•min -1 , 200 mm•min -1 , 250mm•min -1 The resistivity change is kept stable at a constant speed, that is, the fluctuation of the peak resistivity change (ΔR / R0) is almost negligible and the signal waveform remains consistent.
[0132] Fig.10 The sensitivity of the aerogel prepared in Example 1 as a stress sensor. As can be seen from the figure, the aerogel prepared in Example 1 exhibits excellent linear sensitivity in the range of 0 to 300 Pa, and its maximum value can reach 160.93 kPa. -1 In addition, the pressure resolution of the aerogel prepared in Example 1 can reach 4.6 Pa, which has an extremely high pressure resolution and can accurately identify the pressure size.
[0133] Fig.11 The sensitivity of the aerogel prepared in Example 1 as a strain sensor. As can be seen from the figure, the aerogel prepared in Example 1 shows excellent linear sensitivity in the range of 0.01% to 0.19%, and its maximum value can reach GF=3364. In addition, the pressure resolution of the aerogel prepared in Example 1 can reach 0.01% strain, which has extremely high strain resolution and can accurately identify the strain size.
[0134] Fig.12 The sensor response speed of the aerogel prepared in Example 1. As can be seen from the figure, the compression response speed of the aerogel prepared in Example 1 is 11 ms, and the rebound response speed is 38 ms, which shows that the aerogel prepared in Example 1 has a fast pressure response speed and can respond and identify the pressure signal quickly.
[0135] Fig.13 The response lag time of the aerogel prepared in Example 1 at different stress application speeds (15% strain) is shown in the figure. As can be seen from the figure, the fitting straight lines of the actual response time and the theoretical response time of the aerogel prepared in Example 1 almost overlap, the slope is close to 1, and the linear correlation coefficient is 0.9996.
[0136] Fig.14The cyclic signal stability of the aerogel prepared in Example 1. As can be seen from the figure, the aerogel prepared in Example 1 was tested 1000 times under 15% strain, and its signal retention rate can reach 90% of the initial value, showing extremely high signal stability, which is attributed to the excellent elasticity of the prepared aerogel due to the oriented porous structure combined with the unique rigid / flexible molecular segment microstructure regulation.
[0137] Table 1 Table 1 shows the resistance and conductivity of the aerogels prepared by Example 1 and Comparative Example 5. Analysis of the data in Table 1 shows that the preparation order of DF-LCEA aerogel and the polymerization loading order of polypyrrole have a significant effect on its conductive properties. The preferential synthesis of DF-LCEA aerogel can pre-form a uniform pore structure, providing sufficient loading area for pyrrole, so that pyrrole can be in-situ loaded on the pore wall of the aerogel, and then a uniformly distributed conductive network is constructed in the gel network. On the contrary, if pyrrole and ferric chloride are directly introduced during the gel synthesis process, ferric chloride will react with sodium hydroxide to form an iron hydroxide precipitate, which not only consumes ferric chloride as an oxidant and initiator, but also hinders pyrrole from forming an effective conductive path in the gel network. Therefore, the choice of preparation order is crucial to the conductive properties of aerogels.
[0138] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a superelastic aerogel sensing material, characterized in that: The following steps are involved: (1) Adding cellulose and lignin to a urea / alkali mixed solution, after fully dissolving, adding a cross-linking agent, and obtaining a lignin / cellulose hydrogel by chemical cross-linking; (2) immersing the lignin / cellulose hydrogel in water to make it swell; (3) Directional freezing and shaping of the swollen lignin / cellulose hydrogel, and then freeze-drying to obtain a directionally frozen lignin / cellulose composite aerogel; (4) The directional frozen lignin / cellulose composite aerogel is first immersed in a pyrrole / acid mixed solution, then immersed in a ferric chloride / acid mixed solution to induce the in-situ polymerization of pyrrole, and finally freeze-dried to obtain a superelastic conductive lignin / cellulose aerogel.
2. The method for preparing a superelastic aerogel sensing material according to claim 1, characterized in that: The method also includes the following steps: (5) depositing silane on the superelastic conductive lignin / cellulose aerogel by thermal chemical vapor deposition to impart hydrophobicity to the material, thereby obtaining a hydrophobic superelastic aerogel sensing material.
3. The method for preparing a superelastic aerogel sensing material according to claim 1, characterized in that: The cellulose in step (1) is at least one of hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose; The lignin in step (1) is at least one of alkali lignin, lignin sulfonate, enzymatic lignin and solvent-based lignin; The cross-linking agent in step (1) is at least one of epichlorohydrin, N,N-methylenebisacrylamide and glutaraldehyde; The mass ratio of cellulose to lignin in step (1) is (1-4): (1-5); The concentration of the crosslinking agent in step (1) is 3 to 15 wt % in the system of step (1).
4. The method for preparing a superelastic aerogel sensing material according to claim 1, characterized in that: The base in step (1) is at least one of sodium hydroxide and potassium hydroxide; In the urea / alkali mixed solution of step (1), the mass ratio of urea to alkali is (5-15):(5-10), and the total mass concentration of the urea / alkali mixed solution is 15-25%; The ratio of the cellulose to the urea / alkali mixed solution in step (1) is (1-4) g:100 mL.
5. The method for preparing a superelastic aerogel sensing material according to claim 1, characterized in that: The swelling time in step (2) is 6 to 48 hours; The directional freezing method in step (3) is a liquid nitrogen-assisted directional freezing method, specifically placing the swollen lignin / cellulose hydrogel on a copper plate immersed in liquid nitrogen for directional freezing.
6. The method for preparing a superelastic aerogel sensing material according to claim 1, characterized in that: The concentration of pyrrole in the pyrrole / acid mixed solution in step (4) is 0.1 to 2 wt %, and the soaking time is 10 minutes to 12 hours; The concentration of ferric chloride in the ferric chloride / acid mixed solution in step (4) is 0.1 to 3 mol / L, and the soaking time is 0.5 to 12 hours; The pyrrole / acid mixed solution in step (4) is obtained by adding pyrrole to an acid solution and mixing, and the ferric chloride / acid mixed solution is obtained by adding ferric chloride to an acid solution and mixing, and the acid solution is one of a 0.1-1 mol / L hydrochloric acid solution and a 0.1-1 mol / L sulfuric acid solution; The temperature of the ferric chloride / acid mixed solution in step (4) is -5 to 5°C; The freeze drying in step (4) refers to first freezing at -30 to -18°C for 12 to 48 hours and then freeze drying at -50 to -90°C and 1 to 10 Pa for 36 to 52 hours.
7. The method for preparing a superelastic aerogel sensing material according to claim 1, characterized in that: The mass ratio of cellulose to lignin in step (1) is 4:(3-5); The ratio of the cellulose to the urea / alkali mixed solution in step (1) is (2-4) g: 100 mL; The swelling time in step (2) is 6 to 24 hours; The concentration of pyrrole in the pyrrole / acid mixed solution in step (4) is 0.5 to 2 wt %; the soaking time is 10 minutes to 2 hours; The concentration of ferric chloride in the ferric chloride / acid mixed solution in step (4) is 0.5 to 3 mol / L, and the soaking time is 0.5 to 6 hours.
8. The method for preparing a superelastic aerogel sensing material according to claim 2, characterized in that: The thermal chemical vapor deposition method in step (5) is as follows: placing the superelastic conductive lignin / cellulose aerogel and silane in the same container, heating the container, and depositing the silane on the superelastic conductive lignin / cellulose aerogel; The silane is at least one of methyltrimethoxysilane and methyltrichlorosilane; The ratio of the silane to the superelastic conductive lignin / cellulose aerogel is 0.5-2 mL: 0.1-2 g; the heating temperature is 50-80° C., and the heating time is 2-24 hours.
9. A superelastic aerogel sensing material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the superelastic aerogel sensing material according to claim 9.
Citation Information
Patent Citations
ANF / CNT / PPy aerogel fiber sensor as well as preparation method and application thereof
CN114438617A
Underwater super-oleophobic lignin / cellulose high-strength aerogel as well as preparation method and application thereof
CN114854081A
Isotropic multifunctional nanocellulose aerogel as well as preparation method and application thereof
CN117384417A
Blind legacy video artifact reduction
KR1020210038348A